Policy Analysis of Handling COVID-19: Experience China, South Korea, Italy, and Indonesia - Leo Agustino; Harits Hijrah Wicaksana (Journal of Governance, 2020)
This article discusses and analyzes efforts to treat the coronavirus (also known as Coronavirus Disease-19 (COVID-19)) by the governments of China, South Korea, Italy, and Indonesia.  To understand the approaches each country takes is very important to get a clear picture of the efforts, steps, strategies, and policies that are formulated and implemented. To analyze COVID-19 cases in the four countries, the governance analysis framework (GAF) approach from Hamza (in Putra and Sanusi 2019) was used. This approach analyzes four aspects: scope map, stakeholder map, process map, and governance map.  Articles utilizing a qualitative approach using descriptive analysis research methods. Data collection techniques used are library studies in the form of books, journal articles, online and conventional news, and the websites of authoritative institutions.  Several important findings are general and specific, including, first of all, the four countries have the same orientation in handling and controlling the spread of the coronavirus.  Secondly, various actors are actively involved in resolving a pandemic starting with the highest leadership of a country, medical staff and nurses, security agencies, researchers, and so on.  Third, the four countries take their respective ways in solving the COVID-19 problem, but generally, they do a lockdown in addition to the health approach. Fourth, China and South Korea are considered successful examples in handling COVID19, otherwise not with Italy and Indonesia.  The lack of success in Italy and Indonesia is caused by two factors, the lack of seriousness of the government and ignorance of citizens, resulting in slow handling of control and widespread of the deadly coronavirus.